Regularization in quantum field theories - Fabiano, Nicola (Vojnotehnički glasnik / Military Technical Courier, 2022)
Introduction/purpose: The principal techniques of regularization schemes and their validity for gauge field theories are discussed.Methods: Schemes of dimensional regularization, Pauli–Villars and lattice regularization are discussed.Results: The Coleman–Mandula theorem shows which gauge theories are renormalizable.Conclusion: Some gauge field theories are renormalizable, the Standard Model in particular.
Keywords: regularization; renormalization; Gauge Field Theory; Coleman–Mandula Theorem